2017
DOI: 10.5546/aap.2017.eng.5
|View full text |Cite
|
Sign up to set email alerts
|

High blood pressure in school children and adolescents in Argentina over the past 25 years: A systematic review of observational studies

Abstract: Introduction.Over the past years, hypertension has been recognized as an important health problem in the pediatric population. A systematic review of observational studies published between 1988 and 2014 was conducted to estimate the prevalence of high blood pressure and cardiovascular risk factors among children and adolescents in Argentina. Population and methods. A bibliographic search was done in MEDLINE, SciELO, and LILACS to look for studies on high blood pressure prevalence in school children and adoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
2
1
Order By: Relevance
“…Some previous investigations have shown a sex difference in the prevalence of pediatric hypertension. For example, the rates of pre-hypertension and first stage systemic hypertension were observed to be two-fold higher in boys than in girls among school children in a study from Western Ukraine [37], and a systematic review found that boys were more likely to have high BP than girls [40]. In the current study, there was a significantly larger proportion of boys in the hypertensive group than in the normotensive group.…”
Section: Discussioncontrasting
confidence: 38%
See 2 more Smart Citations
“…Some previous investigations have shown a sex difference in the prevalence of pediatric hypertension. For example, the rates of pre-hypertension and first stage systemic hypertension were observed to be two-fold higher in boys than in girls among school children in a study from Western Ukraine [37], and a systematic review found that boys were more likely to have high BP than girls [40]. In the current study, there was a significantly larger proportion of boys in the hypertensive group than in the normotensive group.…”
Section: Discussioncontrasting
confidence: 38%
“…Díaz and Calandra reported that high BP was more prevalent among adolescents than children ≤10 years old [40]. A large cohort study also showed that increasing age was significantly associated with prehypertension and confirmed hypertension [40]. Notably, hypertension seemed to be more common in the obese children than in the non-obese children in all age groups, although the difference in prevalence reached statistical significance only after late childhood.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation